Peers, neighborhoods and immigrant student achievement: Evidence from a placement policy - Olof Åslund; Per-Anders Edin; Peter Fredriksson; Hans Grönqvist (Uppsala University, Department of Economics, 2010)
We examine to what extent immigrant school performance is affected by the characteristics of the neighborhoods that they grow up in. We address this issue using a refugee placement policy which provides exogenous variation in the initial place of residence in Sweden. The main result is that school performance is increasing in the number of highly educated adults sharing the subject's ethnicity. A standard deviation increase in the fraction of high-educated in the assigned neighborhood raises compulsory school GPA by 0.9 percentile ranks. Particularly for disadvantaged groups, there are also long-run effects on educational attainment.
urn:nbn:se:uu:diva-139605
Keywords: J15; I20; Z13; 330; Peer effects; Ethnic enclaves; Immigration; School performance; Migranten; Bildungsniveau; Nachbarschaft; Ethnische Gruppe; Schweden